Ecología trófica y reproductiva de Trichomycterus caliense y Astroblepus cyclopus (Pisces: Siluriformes) en el río Quindio, Alto Cauca, Colombia - Román-Valencia, César (2001)
The trophic and reproductive ecology of catfish (Trichomycterus caliense and Astroblepus cyclopus) was studied in the Quindio River upper Basin, Alto Cauca, Colombia. The pH was neutral, water oxygen content high (8.4 ppm) and temperature in the habitats was 18.63 ºC; both species are nonmigratory and sympatric with four other fish species. The ovaries mature primarily between May and September in T. caliense; between December and May in A. cyclopus. The mean size at maturity is 8.3 cm (standard length) in T. caliense and 6.0 cm (standard length) in A. cyclopus; the sex ratio is 1:1 in T. caliense (X2=3.4, P≥0.05) and in A. cyclopus (X2=1.44, P≥0.1); the fecundity is low (191 and 113 oocytes respectively) and the eggs are small (1.5 and 2.39 mm respectively). The fishes are insectivorous and specialize in Coleoptera, Diptera and Trichoptera; Spearman Rank Correlation Coefficients (rs=0.464) indicated that there are differences (T= 2.5148, P<0.01) between their diets; both taxa did not agree with the expected trophic habits for sympatric species that are morphologically similar and related in the same trophic level.